A chegada de bebês nascidos durante a pandemia de COVID-19 à creche - Apolinário, Thainá Pinto (Universidade Federal de São Carlos, 2023)
The present paper addresses aspects related to the time of arrival of babies to daycare centers, understood here as a period of time for reception and adaptation, after the pandemic of COVID-19. It arose from the curiosity to know how the adaptation in daycare centers was being done for babies who had lived through social isolation; if there were differences in the process and if they presented their own characteristics due to isolation. To reach this goal, a bibliographic research was carried out and a questionnaire was elaborated and answered by two kindergarten teachers. The work is divided into four main moments, which are: the Memorial, the Methodology, the Theoretical Framework, which presents the historical context of the pandemic, the reception in the daycare and child listening, and the Data Analysis reveling that there are differences in behavior of babies who lived in the context of social isolation and only then entered the daycare center and consequently, differences in their processes of adaptation to childhood school. The study presented the importance of a planned welcoming with the families for a better adaptation, and this includes a sensitive listening to what the babies say, verbally or not, so that their wishes are respected in the best possible way.
The arrival of babies born during the COVID-19 pandemic to daycare centers
Keywords: Educação Infantil; Early childhood education; Acolhimento; Reception; Bebês; Babies; Escuta infantil; Child listening; Pandemia; Pandemic; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO